1998
DOI: 10.3141/1617-14
|View full text |Cite
|
Sign up to set email alerts
|

Multiperiod Highway Improvement and Construction Scheduling: Model Development and Application

Abstract: A methodology is presented that emulates the transportation improvement planning process using mathematical optimization techniques. The scheduling problem is formulated as a mixed integer linear program (MILP) and can be considered as a multiperiod network design problem. The three primary model components are discussed: ( a) the input module in which the network, traffic demand, and pool of potential projects are identified over the planning horizon; ( b) the benefits estimation module using network travel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…They concluded that their heuristic method obtained a good solution for a simple highway network while the optimality of the solution could not be guaranteed in the proposed heuristics method. Eldessouki et al (1998) developed a mathematical program to investigate the optimal scheduling of improvement projects for highways where each project involved either increasing capacity or constructing highways. In this mathematical program, the goal was to minimize the total travel time over a few years and entailed the benefit estimation of each combination of projects in a traffic network in terms of the travel time savings considering the road construction cost.…”
Section: Planning Contextmentioning
confidence: 99%
“…They concluded that their heuristic method obtained a good solution for a simple highway network while the optimality of the solution could not be guaranteed in the proposed heuristics method. Eldessouki et al (1998) developed a mathematical program to investigate the optimal scheduling of improvement projects for highways where each project involved either increasing capacity or constructing highways. In this mathematical program, the goal was to minimize the total travel time over a few years and entailed the benefit estimation of each combination of projects in a traffic network in terms of the travel time savings considering the road construction cost.…”
Section: Planning Contextmentioning
confidence: 99%
“…The same regular intervals can be used as the time-basis for establishing schedules of improvement. A possible approach for determining these schedules is contained in El Dessouki et al (1998).…”
Section: Model Limitationsmentioning
confidence: 99%
“…Therefore, the classification of these criteria must be performed so that equipotential and univalent criteria could be placed in one group. Using the integer planning and by implementing the network design problem (NDP), Eldessouki et al (1998) Case n Accident for constructing each piece of network in the way construction prioritization of a network (Eldessouki et al, 1998). However in the present research, more criteria can be considered using the AHP method.…”
Section: Bypass Priority Model Pillars In the Networkmentioning
confidence: 99%